2018
DOI: 10.1002/pssb.201800027
|View full text |Cite
|
Sign up to set email alerts
|

Topological Phases of Chalcogenide Glasses Encoded in the Melt Dynamics

Abstract: Select Raman scattering and modulated differential scanning calorimetry (DSC) experiments on specially homogenized binary GexSe100–x and GexS100–x chalcogenide glasses, supported by ab initio MD simulations are undertaken. In both chalcogenides, the glasses exhibit a super‐strong behavior (with a melt fragility index, m(x) < 20) in the 20(1)% < x < 26(1)% composition range, defining the fragility window, and with m(x) > 20 as one goes away from the fragility window. Remarkably, molecular dynamics (MD) simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 70 publications
(124 reference statements)
0
10
0
Order By: Relevance
“…These results suggest that the intermediate phase is encoded in the medium-range (rather than short-range) order structure of C-S-H. The fact that the typical repetition distance is minimum in the intermediate phase can be related to the fact that intermediate-phase glasses have been shown to exhibit an optimal space-filling tendency (for instance, several chalcogenide glasses exhibit a minimum in molar volume in the intermediate phase) (Rompicharla et al, 2008;Boolchand et al, 2018). This can be understood from the fact that, due to their low connectivity, flexible networks tend to present large rings or terminating bonds, which decreases the packing efficiency of the atoms.…”
Section: Structural Signatures Of the Intermediate Phasementioning
confidence: 94%
See 1 more Smart Citation
“…These results suggest that the intermediate phase is encoded in the medium-range (rather than short-range) order structure of C-S-H. The fact that the typical repetition distance is minimum in the intermediate phase can be related to the fact that intermediate-phase glasses have been shown to exhibit an optimal space-filling tendency (for instance, several chalcogenide glasses exhibit a minimum in molar volume in the intermediate phase) (Rompicharla et al, 2008;Boolchand et al, 2018). This can be understood from the fact that, due to their low connectivity, flexible networks tend to present large rings or terminating bonds, which decreases the packing efficiency of the atoms.…”
Section: Structural Signatures Of the Intermediate Phasementioning
confidence: 94%
“…Interestingly, isostatic chalcogenide glasses belonging to the intermediate phase exhibit some unique properties, namely a reversible glass transition (Boolchand et al, 2001;Chakravarty et al, 2005), weak relaxation and aging (Chakravarty et al, 2005;Chen et al, 2010), low propensity for creep (Bauchy et al, 2017), anomalous mechanical properties (Varshneya and Mauro, 2007;Bauchy et al, 2016a), superstrong behavior (Boolchand et al, 2018), optimal space-filling tendency (Phillips, 2006;Rompicharla et al, 2008), and stress-free character (Wang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It helps one understand how homogeneity of melts/glasses is intimately tied to the observation of the IP in these glasses. Melt/glass homogenization is precursive to observation of a sharp squarewell like reversibility window permitting one to fix the three TPs (Boolchand et al, 2018).…”
Section: Aging Of the Reversibility Window In Fully-with Partially-homentioning
confidence: 99%
“…These phases have now been observed in Chalcogenides‐, 6,7 , modified oxides, 8,9 , Heavy metal oxide‐, 10 and Solid electrolyte 11 glasses. Recent studies have further revealed that melt dynamics 12 are closely correlated to these phases, with super‐strong melts giving rise to IP glasses upon cooling to T g .…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that in the IP the molecular structure is dominated by LCs with LRs and SRs comprising a minority. The result permits one to reconcile the high configurational entropy of that phase, which leads that phase to display qualitatively suppressed aging 13 or high stability 12,22 . In section 2 we discuss the Materials and Methods followed by the experimental results in Section 3, and select salient issues discussed in Section 4.…”
Section: Introductionmentioning
confidence: 99%